Problematizando as tempestades solares: uma sequência para ensinar sobre raios cósmicos - Fragozo, Valmir Galvão (Universidade Federal de São Carlos, 2025)
This work presents the development and implementation of a Didactic Sequence (DS) aimed at teaching Modern and Contemporary Physics in High School, with emphasis on the topic of Cosmic Rays. The teaching–learning process was structured using the pedagogical framework of the Three Pedagogical Moments (3PM), emphasizing features such as dialogicity and problematization in the design of activities. The sequence begins with the problematization of solar storms as a starting point to contextualize concepts of particle physics and to introduce the term "Cosmic Rays" into the students' context. As an educational product of this research, a DS and its associated activities were developed, including questionnaires, essay proposals, study guides, a Kahoot activity, and a word search. During the design and implementation, it was necessary to make adaptations to the traditional 3PM structure to better align the methodology with the selected concepts and the characteristics of the target audience. The DS was applied in a private school with 12th-grade (senior) high school classes, involving dialogic activities such as model construction, essay writing, and analysis of scientific phenomena, fostering active student participation. Based on the analysis of field notes and the applied activities, student engagement was evident. The adaptations allowed for greater fluidity in lesson development and contributed to active participation, fostering connections between the studied phenomena and students' daily lives, as well as facilitating the understanding of abstract concepts in Modern Physics. Thus, the DS proved to be an alternative to the traditional transmissive teaching of Physics, with potential for selective application of some of the developed activities.
Problematizing solar storms: a sequence for teaching about cosmic rays
Keywords: Física moderna; Raios cósmicos; Ensino de ciências; Modern Physics; Cosmic rays; Science Education; Three Pedagogical Moments; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS EXATAS E DA TERRA::FISICA; 4. Educação de Qualidade